Blood Pressure Overview of Hypertension Patients With Complementary Therapy Implementation of Tomato Juice in RT 05 RW 04 Pulo Gebang Village, Cakung District, East Jakarta - Dayuningsih, Dayuningsih; Gobel, Satria; Maisaroh, Siti (JOURNAL EDUCATIONAL OF NURSING(JEN), 2022)
Complementary therapy is a health method that is applied in conjunction with conventional medicine to improve the health of patients. These techniques include acupuncture, massage, and the use of herbs. Complementary therapy should be used safely and effectively as a complement to care, especially in the context of family nursing care. Family nurses have an important role in helping families overcome health problems in sick family members, one of which is a family member with hypertension. Hypertension or high blood pressure is a condition where blood pressure exceeds 140/90 mmHg. One of the complementary therapies to lower blood pressure is the administration of tomato juice. The author uses a descriptive case study design with a nursing process approach to hypertensive patients. The author will look at the description of nursing care for hypertensive patients with the administration of tomato juice to determine whether it can lower blood pressure. When the initial blood pressure measurement was 150/98 mmHg and after complementary therapy with tomato juice for 4 days given twice a day in the morning and evening, blood pressure decreased to 145/92 mmHg.